ISPC Commentary on the Revised Proposal for CRP5 - October 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the revised proposal for CRP 5: Water, Land and Ecosystems